The State Support of Grant Activities in Ukraine - Motuzka, O. M.; Parkhomenko, V.V. (Statistics of Ukraine, 2023)
The notion “grant project” is elaborated on, with investigating the types of state support to grant activities in Ukraine. It is argued that the number of grant programs in Ukraine has been constantly increasing. This type of targeted financing can be received as part of national initiatives and from private companies or international organizations. It is substantiated that the importance of grants in the war and postwar time will be rising, which is quite logical given the increasing scopes and complexity of problems in economic and social sphere. Grants offer a good way of facing these problems: the competitive approach allows for selecting the best, the most promising and productive entrepreneurs capable to achieve the goals in an efficient manner. The number of potential donors and funds allocated for them continue growing. It should be noted that grants are a conventional and widespread practice of funding in EU. It means that businesses have to carefully consider this potential channel of funding. The following programs for support of Ukrainian business were implemented in IV quarter 2023: micro-grants for creating one’s own business; grants to operate a processing factory; funds to operate a greenhouse facility; grants for a startup; grants for veterans and their family members. The peculiarity of each of the above programs are analyzed. The program eRobota (eWork) launched 1 July, 2022 and aimed at stimulation of entrepreneurial activities and job creation proved to be a most ambitious one: its total funding in 2023 amounted to 1,800,000,000 UAH. The principal requirements to grant recipients are highlighted: absence of business activities on the temporarily occupied territories and in the Russian Federation, not being a sanctioned entity, absence of bankruptcy procedures and debts to the state. The overwhelming majority of recipients got micro-grants that were invested in acquisitions of equipment required for business operation. The most demanded sectors where grant recipients operate are wholesale and retail trade, repair of automobile vehicles, temporary accommodation and meals, manufacturing industry, medical and social aid.